Diseño deun área de recreación turística en la cascada "Sa Federico" de la parroquia Fedérico Intriago, cantòn valencia, año 2019 - Cedeño Morales, Mercedes Isabel (2019)
Nowadays, the recreation areas have become tools that allow the use of the existing touristic resources, in the natural spaces, contributing to promote the economic growth of the comunities, entertaiment of people and the touristic development of the site. In this research, the latest condition of the waterfall was determined, through a diagnosis of the current situation. It was possible to notice the lack of tourist facilities that could contribute the scattering of visitors. Also, a great diverse of existing species were able to be identified in the area. In addition, surveys carried out at the area, stated the 67% of satisfaction with the implementation of tourist facilities. Finally, a tourist recreational area was designed at the “San Federico” waterfalls in the Federico Intriagos parish. This will contribute effectively to the socio-economic and cultural growth, not only to the community, but also to the surrounding towns near the attraction. It will grant them a touristic space which will be useful as an integrator to the habitants of such place. Keywords: Recreation, tourist facilities, natural attractions, design, areas